Constraining the z ∼ 1 Initial Mass Function with HST and JWST Lensed Stars in MACS J0416.1−2403 - Sung Kei Li; Jose M. Diego; Ashish K. Meena; Jeremy Lim; Leo W. H. Fung; Arsen Levitskiy; James Nianias; Jose M. Palencia; Hayley Williams; Jiashuo Zhang; Alfred Amruth; Thomas J. Broadhurst; et al. (The Astrophysical Journal, 2025)
Our understanding of galaxy properties and evolution is contingent on knowing the initial mass function (IMF), and yet to date the IMF is constrained only to local galaxies. Individual stars are now becoming routinely detected at cosmological distances, where luminous stars such as supergiants in background galaxies strongly lensed by galaxy clusters are temporarily further magnified by huge factors (up to 10 ^4 ) by intracluster stars, thus being detected as transients. The detection rate of these events depends on the abundance of luminous stars in the background galaxy and is thus sensitive to the IMF and the star formation history (SFH), especially for the blue supergiants detected as transients in the rest-frame ultraviolet/optical filters. As a proof of concept, we use simple SFH and IMF models constrained by spectral energy distributions (SEDs) to see how well we can predict the Hubble Space Telescope and James Webb Space Telescope transient detection rate in a lensed arc dubbed “Spock” ( z = 1.0054). We find that demanding a simultaneous fit of the SED and the transient detection rate places constraints on the IMF, independent of the assumed simple SFH model. We conclude that our likelihood analysis indicates that the data definitively prefers the “Spock” galaxy to have a Salpeter IMF ( α  = 2.35) rather than a top-heavy IMF ( α  = 1)—which is thought to be the case in the early universe—with no clear excess of supergiants above the standard IMF.